Marketing Strategy Scenario Planning to Increase Digital Market Penetration (Project Based: PT Asuransi Tri Pakarta) - Juniar Firdaus Imran; Yos Sunitiyoso (Journal Research of Social Science, Economics, and Management, 2026)
The main challenge faced by PT Asuransi Tri Pakarta (TRIPA) is the low acquisition of new customers through digital channels, despite significant investments in digital infrastructure such as the TRIPA Smart app and omnichannel systems. This gap is driven internally by limited brand awareness and externally by intensifying competition from Insurtechs and traditional insurers. To navigate this uncertainty, the study applies scenario planning to analyze future environments and formulate adaptive marketing strategies for boosting digital market penetration. The research aims to identify root causes, analyze the current situation, formulate future scenarios for the next three to five years, and develop adaptive marketing strategies for each potential scenario.This research employs a descriptive qualitative approach, with data collected through semi-structured interviews involving key stakeholders, including company management, the Head of the Indonesian General Insurance Association (AAUI), regulators, and customer representatives. The analysis and discussion will present an examination of the internal situation (using the STP and SWOT frameworks) and the external situation (using the PESTEL and Porter’s Five Forces frameworks), which will then be used to identify driving forces and critical uncertainties. From there, plausible scenarios will be constructed and described narratively, followed by testing to formulate a flexible digital marketing strategy. This research is expected to provide practical contributions to TRIPA’s management in formulating proactive and resilient marketing policies, as well as academic contributions by applying scenario planning in the context of the Indonesian insurance industry.